A local search heuristic for nurse assignment problems with personal preferences - André, Maria Valéria de Carvalho; Silva, Hedivigem Luana Rodrigues da; Silva, Yuri Laio Teixeira Veras (Brazilian Journal of Production Engineering, 2024)
Recently, research into healthcare optimization has experienced exponential growth, arousing significant interest from researchers and healthcare organizations. This increase in interest is driven by the complexity and relevance of the challenges faced by society, and is directly related to the growing need to improve processes and the search for greater efficiency in healthcare systems on a global scale. The aim of this study is to develop an optimization approach, based on computational heuristic, to perform the planning and assignment of nurse professionals in hospital sectors in order to maximize both the personal preferences of the professionals and the efficiency of health care services. The proposed method uses a heuristic optimization algorithm based on local search with solution perturbation mechanisms and efficient search neighbourhoods. The computational results showed that the method could perform efficient assignments of nursing professionals in hospital sectors, optimizing job satisfaction and quality of service provided. In conclusion, the study evidenced that the developed method allows efficient management and assignment of nurse professionals in hospital settings, achieving scientific and practical contributions to the areas of healthcare optimization and hospital administration.
Keywords: Hospital Administration; Heuristics; Local Search